Australian Trade Mark Law, 3rd Edition - Burrell, RG; Handler, RBM (LexisNexis Australia, 2024)
Australian Trade Mark Law 3rd edition, provides a comprehensive overview of trade mark law in Australia. It moves beyond a purely descriptive account of existing legislation and case law to help readers to view and question the law through a critical lens. It explores the functioning of the trade mark system as well as the decisions made. As well as critically assessing how the trade mark system could work better in the future, Australian Trade Mark Law presents comparative material that illustrates how other jurisdictions deal with particular issues and problems. Features Clear, accessible guidance that follows the lifecycle of a registered trade mark The use of images of trade marks throughout the book to illuminate key cases and doctrines Written by two leaders in the field